Annual Review of Development Effectiveness 2006 : Getting Results - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This Annual Review of Development Effectiveness (ARDE) brings together evaluative evidence from the recent work of the Independent Evaluation Group of the World Bank to address three questions surrounding this results chain in countries, with a particular focus on the Bank's role in the chain: (a) how effectively has economic growth translated into poverty reduction in Bank-assisted countries, and what factors have affected these results? (b) what factors have led to high-quality results in areas that deliver services to the poor? (c) what measures help raise the accountability of public institutions responsible for delivering and sustaining results? The report identifies features that characterize the country experiences and assistance programs that have delivered results: (1) effective programs have a twofold focus: they emphasize both the ingredients of growth and the measures that help the poor share in the growth process; (2) they build on a realistic and well-informed assessment of the political commitment and capacity of the recipient to deliver results, and they emphasize coalition and capacity building to help attain results; (3) they combine sustained engagement with clear intermediate milestones; and (4) they emphasize improved transparency and local control of public institutions, factors that spur these institutions to deliver results.